2011
DOI: 10.1016/j.econlet.2011.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The unemployment effect of exchange rate volatility in industrial countries

Abstract: Using data on 17 industrial countries from 1982 to 2003 and controlling for a wide array of factors, this paper finds that higher exchange rate volatility increases the unemployment rate.The magnitude of the effect is small. The results are robust to variations in specification.JEL classification: E24, F31, F41, J64

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
(5 reference statements)
1
24
0
Order By: Relevance
“…Evidence of an adverse impact on productivity, domestic investment, consumption and growth can be found in papers by Braun and Larrain (2005), Aghion et al (2009), Schnabl (2009, Bahmani-Oskooee and Xi (2011) and Bahmani-Oskooee and Hajilee (2013). Feldmann (2011) finds evidence that higher exchange rate volatility raises the unemployment rate in a country. The evidence on the impact of exchange rate volatility on international trade is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence of an adverse impact on productivity, domestic investment, consumption and growth can be found in papers by Braun and Larrain (2005), Aghion et al (2009), Schnabl (2009, Bahmani-Oskooee and Xi (2011) and Bahmani-Oskooee and Hajilee (2013). Feldmann (2011) finds evidence that higher exchange rate volatility raises the unemployment rate in a country. The evidence on the impact of exchange rate volatility on international trade is mixed.…”
Section: Introductionmentioning
confidence: 99%
“…Their finding is that variability of the domestic exchange rate with respect to the US Dollar and the Euro are significantly related to higher unemployment rates in Brazil and Argentina. Analysing a panel data set of 17 industrial countries,Feldmann (2011b) confirms that real effective exchange rate volatility (measured on the basis of a GARCH(1,1) model) is positively linked to unemployment rates. Inflation variability and exchange rate variability might be highly relevant as central bank transparency could have an influence on those two variables.…”
mentioning
confidence: 72%
“…Trade theory suggest that a depreciation of real exchange rate increases the competitiveness of the country's exports and hence the demand for labour increases. On the other hand, a depreciation of real exchange rate increases the cost of intermediate inputs which might offset the first effect such affect production level adversely which tends to reduce competitiveness of the country export and hence, demand for labour decreases (Demir, 2010;Feldmann, 2011).…”
Section: Article History Abstractmentioning
confidence: 99%
“…Trade theory suggest that a depreciation of real exchange rate increases the competitiveness of the country's exports and hence the demand for labour increases. On the other hand, a depreciation of real exchange rate increases the cost of intermediate inputs which might offset the first effect such affect production level adversely which tends to reduce competitiveness of the country export and hence, demand for labour decreases (Demir, 2010;Feldmann, 2011).In Nigeria, statistics revealed that between 2013 and 2014, the unemployment rate increased from 16.7 to 17.1, despite an increase in annual real GDP from 5.4% to 6.3% with a decrease in the annual inflation from 8.5% to 8% whereby an improvement of real effective exchange rate occurred from 74.20 and 69. 51.…”
mentioning
confidence: 99%